Strategi Investasi Formula Ajaib: Bukti Empiris dari Bursa Efek Indonesia - Rakim, Aditya Achmad; Leni Wijaya, Dahyang Ika (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The magic formula investment strategy portfolio selection concept is proven to be effective on different share markets around the world. This formulation ranks firms by combining the ratio of return on capital and earning yield on the selected portfolio so that the expected returns can beat market. The portfolio built using the magic formula strategy was able to outperform the benchmark index by an average of 13.23% and 5.32% between June 2011-May 2021. The magic formula portfolio is built supports the signaling theory. This study finding the answer whether the portfolio formulation strategy that built is able to outperform the index benchmark. The JCI index was chosen as the benchmark. Focus of this research is limited to it only covers firms included in the SMC Composite index, so generalization of research results needs to be carefully.